POPULATION TRENDS OF APHIS GOSSYPII GLOVER (HOMOPETRA: APHIDIDAE) ON BRINJAL IN RELATION TO CLIMATIC FACTORS AND ACTIVITY OF PREDATORS - SHAH, M.A. SATTAR; CHANU, M. CHINAMEN; SINGH, T.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The population trends of Aphis gossypii Glover were studied for two consecutive cropping seasons (2005 & 2006) on brinjal, Solanum melongena L. var. Pusa Purple Long. The study revealed that the infestation of this aphid started from the first week of March and extended up to last week of June in both the cropping seasons. The peak population of the aphid was recorded during May with maximum abundance of 216.45 and 19746 aphids /sampling unit during 2005 & 2006, respectively. The aphid was associated with eight species of aphidophagus predators such as coccinellids, syrphids and occasionally hemerobiids. Increased in aphid density coincided with increases in density and diversity of predators. No parasitoides were found to be associated with this aphid. The co-efficient of correlations in numerical abundance of A gossypii on brinjal were determined with climatic factors and predators.